Since both of the equations are equal to y...set them equal to each other.. So it will then be
x^2+3=x+5
-3 -3
x^2=x+2 ---> x^2-x-2
(x-2) (x+1)
x=2,-1
I don't understand the question
Answer:
33
Step-by-step explanation:
The product of the secant segment lengths is a constant.
... TC×CV = UC×CW
... 14(2x+2) = 12(2x+5) . . . . substitute the values from the diagram
... 28x +28 = 24x +60 . . . . eliminate parentheses
... 4x = 32 . . . . . . . . . . . . . . add -28-24x
... x = 8 . . . . . . . . . . . . . . . . divide by 4
UW = 12 + 2x + 5 = 17+2·8 . . . . UW = UC + CW
UW = 33
the asnwer is 14 feet 5 inches because you add feet and then inches